THE ROLE OF INTERNET JOURNALISM IN THE GLOBAL INFORMATION SPACE - Tokhirova Sevinch Akram kizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: Internet journalism has become a pivotal force in shaping the global information space by enabling fast, accessible, and borderless dissemination of news. It has transformed how people access, share, and interact with information, fostering global awareness and interconnectedness. This article explores the role of internet journalism in the global context, emphasizing its impact on information flow, cultural exchange, and democratic participation while addressing challenges such as misinformation, digital divides, and information overload.